Heading in a new direction? Recommendations for future research on patient decision aids. Issue 5 (May 2019) - Herrmann, Anne; Hall, Alix; Zdenkowski, Nicholas; Sanson-Fisher, Rob
Highlights: Decision aids are not commonly used in clinical practice. Research is needed to inform when and how to use decisions aids. We reviewed the methodology of current effectiveness trials. We make suggestions for potential next steps of decision aid research. This can help move towards implementation trials to increase their adoption. Abstract: Decision aids can improve a number of patient outcomes, but they are not commonly used in clinical practice. This commentary paper provides suggestions for potential next steps of decision aid research, with the aim to facilitate their implementation. We suggest to further standardise clinically meaningful outcomes and outcome measures that should be used to examine the impact of decision aids. Second, using mediation analysis and active control groups could help tease out and explore variables that influence decision aids' effectiveness to help healthcare providers decide when and how to use them in clinical practice. Third, effectiveness trials should be clearly reported and replicated to investigate under what circumstances decision aids work best. Specific checklists for decision aid trials should be used to ensure that all relevant factors are reported in detail. Addressing the above issues will help identify what specific components of decision aids are effective and should be implemented. We can then move towards conducting implementation trials which help increase the use of decision aids in "real-world" healthcare.